Gobernanza y Políticas Públicas para la educación en el contexto chileno (Ariadna Ediciones, 2024)
This book is a result of the postdoctoral program Governance and Public Policies in Higher Education version 2022-2023 of the University of Alcalá of Spain (UAH) in collaboration with the Organization of Ibero-American States for Education, Science and Culture (OEI). This book includes fifteen chapters, written by researchers, and is the result of part of their research carried out in the program. They wish to express their experiences and studies associated with the topics of governance and public policies.